The changes in psychological symptoms of COVID-19 patients after “re-positive” - Wang, Xing; Fan, Qinyi; Li, Yunyue; Xiao, Junjian; Huang, Yanyan; Guo, Tiantian; Chen, Hongguang; Li, Mengqian (Frontiers in Psychiatry, 2022)
Background Previous studies have showed that individuals infected with COVID-19 were more likely to report psychological symptoms. However, little is known about the changes from testing positive to negative to positive again. Methods This survey was conducted through the questionnaires including the 7-item Generalized Anxiety Disorder (GAD-7), the 9-item Patient Health Questionnaire (PHQ-9), as well as the Self-Rating Scale of Sleep (SRSS) to explore the psychological status of COVID-19 and re-positive cases. ″re-positive″ is defined as a positive RT-PCR test at any time during the recovery period after testing negative. Results A total of 94 COVID-19 patients presented the prevalence rates of anxiety, depression, insomnia, and any of the three psychological symptoms being 26.6, 8.6, 12.8, and 31.9%, respectively. Among these, 32 cases were re-tested positive during the recovery period, with the prevalence rates of anxiety, depression, insomnia, and any of the three psychological symptoms being 21.9, 18.7, 31.2, and 37.5%, respectively. The psychological status after re-positive showed a significant decrease in anxiety (P = 0.023), an increase in depression, and a significant rise in insomnia (P = 0.035). For those with no psychological symptoms during initial-positive, after re-positive, 5.88% reported anxiety, 5.88% reported depression, and 11.76% reported insomnia. For those who experienced only anxiety symptoms during initial-positive, after re-positive, 33.3% reported depression, and 33.3% reported insomnia. Conclusions Our findings encompassed the urgent concern for anxiety in initial-positive COVID-19 patients, depression in re-positive COVID-19 patients, and insomnia in both initial and re-positive patients, hence enabling targeted interventions for appeasing the psychological burden of COVID-19 patients.